Relationship of water quality with bacterial disease in Dumbo catfish (Clarias gariepinus L) in culture ponds in Palembang city - Leni Apriani; Novi Susanti; Gustriana Gustriana (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
This study aims to determine water quality related to the occurrence of bacterial diseases of “Dumbo” catfish (Clarias gariepinus) reared in the pond. Field study was conducted at Bukit Lama and Bukit Baru Ilir Barat I Bukit Besar Palembang and laboratory studies was conducted at the Laboratory of Fish Quarantine Center of SMB II Palembang. The study was carried out at 3 representative locations. The parameters measured were: physical (temperature), chemical (dissolved oxygen, pH, ammonia, nitrate, and nitrite). The results of physical and chemical parameters indicated that the average value of all study sites was temperature of 30.30 to 30.73 º C, pH 6.5 - 7.0, ammonia of 0.01 to 1.6 ppm, dissolved oxygen of 0.87 to 3.4 ppm, nitrate of 1.4 to 3.2 ppm, nitrite of 0.01 ppm. The results of the identification of bacteria found 4 species, namely: Aeromonas hydrophila, Yersinia enterocolitica, Vibrio anguillarum, Pseudomonas aeruginosa which are pathogenic bacteria on fish. The dominant bacteria found during the study was Aeromonas hydrophila. The results of the study showed that the water quality of “Dumbo” catfish ponds (C. gariepinus) in Bukit Lama and Bukit Baru Ilir Barat 1 Palembang is not recommended for aquaculture.